2023
DOI: 10.2147/jhc.s391755
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nomograms Based on Gamma-Glutamyl Transpeptidase-to-Lymphocyte Ratio Predict Prognosis of Hepatocellular Carcinoma Patients After Hepatectomy

Abstract: Background The prediction of prognosis of hepatocellular carcinoma (HCC) is of great significance in improving disease outcome and optimizing clinical management, while reliable prognostic indicators are lacking. This study was conducted to develop readily-to-use nomograms for prognosis prediction of HCC after hepatectomy. Materials and Methods Data of eligible patients were collected and analyzed retrospectively. Independent prognostic factors were identified by Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This association can be attributed to the fact that abnormal liver function and cholestasis often lead to elevated levels of GGT, a component of the GPR. Elevated GGT levels have been implicated in tumor formation and progression through various mechanisms [ 15 ]. Consequently, previous studies have recommended utilizing the GGT to platelet ratio as a prognostic marker for HCC patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association can be attributed to the fact that abnormal liver function and cholestasis often lead to elevated levels of GGT, a component of the GPR. Elevated GGT levels have been implicated in tumor formation and progression through various mechanisms [ 15 ]. Consequently, previous studies have recommended utilizing the GGT to platelet ratio as a prognostic marker for HCC patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current corpus of scienti c literature posits that GGT plays a cardinal role in contributing to unfavorable outcomes in oncology patients by stimulating the generation of reactive oxygen species (ROS) within the neoplastic microcosm, thereby spurring the proliferation, expansion, and in ltration of the malignant growth [31]. A surge in GGT concentrations may be discerned in a diversity of hepatobiliary maladies, cementing its reputation as a sensitive and invaluable clinical barometer for these disorders [32][33][34]. Upon the event of biliary obstruction, GGT measurements may skyrocket, reaching between 5 to 30 times the standard parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that these indicators can effectively evaluate the prognosis of HCC patients undergoing surgical resection [ 16 21 ]. Other blood biomarkers combined inflammation and liver function, including neo‐Glasgow prognostic score (neo-GPS) [ 22 ], aspartate aminotransferase-to-lymphocyte ratio index (ALRI) [ 23 ], gamma-glutamyl transpeptidase-to-lymphocyte ratio (GLR) [ 24 ], CRP-to-albumin ratio (CAR) [ 19 ]have also been reported as independent prognostic predictors for HCC. So far, there are limited studies on the prognostic values of these indicators for unresectable HCC patients receiving anti-PD-1 antibody treatments.…”
Section: Introductionmentioning
confidence: 99%